The Economy in transition : restructuring to 1989 - Economic Monitoring Group (Wellington, New Zealand : New Zealand Planning Council, 1989)
This book explained the economy development and the restructuring of New Zealand economy.
NZ89-October
Includes bibliographical references: p. 193-196.
oo 09/04/2019
Loans
Keywords: Economic development; Economic growth; Economic conditions; New Zealand